2015
DOI: 10.1001/jama.2015.1671
|View full text |Cite|
|
Sign up to set email alerts
|

Antiplatelet Therapy Duration Following Bare Metal or Drug-Eluting Coronary Stents

Abstract: Importance Despite antirestenotic efficacy of coronary drug-eluting stents (DES) compared with bare metal stents (BMS), the relative risk of stent thrombosis and adverse cardiovascular events is unclear. Although dual antiplatelet therapy (DAPT) beyond one year provides ischemic event protection following DES, ischemic event risk is perceived to be less following BMS and the appropriate duration of DAPT following BMS is unknown. Objective To compare: (1) rates of stent thrombosis and major adverse cardiac an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 23 publications
1
55
1
2
Order By: Relevance
“…The DAPT Study, the design of which has been previously described, 18 compared 30 versus 12 months of thienopyridine therapy (clopidogrel or prasugrel) when prescribed in addition to aspirin following coronary stenting with either DES 17 or bare metal stents 19 for the prevention of stent thrombosis or major adverse cardiovascular and cerebrovascular events, a composite of all-cause mortality, MI, or stroke (MACCE; ClinicalTrials.gov NCT00977938). Each participating institution's ethics committee approved the study, and each patient gave written informed consent.…”
Section: Methods Designmentioning
confidence: 99%
“…The DAPT Study, the design of which has been previously described, 18 compared 30 versus 12 months of thienopyridine therapy (clopidogrel or prasugrel) when prescribed in addition to aspirin following coronary stenting with either DES 17 or bare metal stents 19 for the prevention of stent thrombosis or major adverse cardiovascular and cerebrovascular events, a composite of all-cause mortality, MI, or stroke (MACCE; ClinicalTrials.gov NCT00977938). Each participating institution's ethics committee approved the study, and each patient gave written informed consent.…”
Section: Methods Designmentioning
confidence: 99%
“…), using datasets whenever possible that excluded patients receiving BMS. Of note, several RCTs contained summary statistics for patients treated with BMS or DES, but 2 RCTs presented separate summaries for patients receiving DES only, 14,15,23,29 and these were used in the present analysis.…”
Section: Duration Of Dapt After Des Implantationmentioning
confidence: 99%
“…If, after discussion with a cardiologist, DAPT needs to be modified for a non-cardiac procedure during the 12 months following coronary stent insertion, then only the P2Y12 inhibitor should be discontinued (for 5 days prior to the procedure)-the aspirin should be continued; 6. The situation is further complicated by recent data (DAPT trial) 51 which suggests that certain patients may benefit from an extension of their DAPT till at least 30 months. This study reported fewer ischaemic events in patients receiving DAPT up till 30 months than those discontinuing at 12 months, but at the cost of a higher risk of (non-fatal) bleeding; 7.…”
Section: Developments In Antiplatelet Therapymentioning
confidence: 99%